The Analysis of Biomechanics and Ocular Motilities through Dynamic Image Processing Methods. (2015) - Gabor, Dan; Baritz, Mihaela; Cristea, Luciana; Repanovici, Angela
Abstract: The ocular and motor equilibrium of the visual system is ensured by normal ocular movements, and any neural-, ocular and motor disorders, any visual behaviour or non-verbal communication can be traced through the analysis of trajectories recorded through different methods. The theoretical background of the eye movements' analysis is founded on the establishment of movement equations of the eyeball, as they consider it a solid body with a fixed point. The exterior actions, the order and execution of the movements are ensured by the neural and muscular external system and thus the position, stability and movements of the eye can be quantified through the method of reverse kinematic. The purpose of these researches is the development of an acquisition methodology, data processing and recording regarding the eye movements. The methodology developed in this research is based on the image acquisition of the eye movements by means of an eye tracking-type device on visible radiation, through which the position of the visual system related to a series of static and dynamic stimuli showed on the monitor is being analysed. Also, the eye movements are being tracked with the help of a video camera, and the appropriate trajectories are recorded through successive positions of the pupil centre, which are related to the visual stimuli. Following these recording, the positions of the eyes, the disorders of the ocular and motor equilibrium and the visual behaviour of the target group could be analysed, in relation to the succession of stimuli established according to the procedures in the field. A first important aspect established through this research consists of the determination of the correspondence from the movement equation of the visual system and its illumination degree. An experimental methodology for analysing the interdependencies from the video images of the visual system and the level of stimuli was also developed.